Short-term evolutionary implications of an introgressed size-determining supergene in a vulnerable population - Pierre Lesturgie; John S. S. Denton; Lei Yang; Shannon Corrigan; Jeff Kneebone; Romuald Laso-Jadart; Arve Lynghammar; Olivier Fedrigo; Stefano Mona; Gavin J. P. Naylor (Nature Communications)
Abstract The Thorny Skate (Amblyraja radiata) is a vulnerable species displaying a discrete size-polymorphism in the northwest Atlantic Ocean (NWA). We conducted whole genome sequencing of samples collected across its range. Genetic diversity was similar at all sampled sites, but we discovered a ~ 31 megabase bi-allelic supergene associated with the size polymorphism, with the larger size allele having introgressed in the last ~160,000 years B.P. While both Gulf of Maine (GoM) and Canadian (CAN) populations exhibit the size polymorphism, we detected a significant deficit of heterozygotes at the supergene and longer stretches of homozygosity in GoM population. This suggests inbreeding driven by assortative mating for size in GoM but not in CAN. Coalescent-based demographic modelling reveals strong migration between regions maintaining genetic variability in the recombining genome, preventing speciation between morphs. This study highlights short-term context-dependent evolutionary consequences of a size-determining supergene providing new insights for the management of vulnerable species.